MODERN TRENDS IN THE DEVELOPMENT OF PERSONAL SERVICE ENTERPRISES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the issue of trends in the development of personal services enterprises in modern conditions. The analysis shows changes in the principles  of the placement of enterprises in the areas of new buildings, as well as the need to improve approaches to planning the retail and personal infrastructure of residential areas. The author studied the factors influencing the behavior of consumers of services.